Which dimension of income distribution drives crime? Evidence from the People's Republic of China - Chen Wang; Guanghua Wan; Xueliang Zhang (Asian Development Bank Institute (ADBI), 2017)
Income distribution is perceived to affect crime (Becker 1968; Thurow 1971; Merlo 2003). Consequently, economists have been modeling crime-employing inequality indicators as one of the explanatory variables, yielding mixed results. This paper argues that income polarization rather than inequality should be taken into account in the context of crime analysis. Technically, in addition to income gaps as captured by inequality indicators, the recently developed polarization index of Duclos, Esteban, and Ray (2004) also measures social segregation, which implies immobility and alienation, both of which are closely related to social tensions and conflicts. Thus, this polarization index is expected to be a better variable in explaining crime. To substantiate our arguments, provincial panel data from the People's Republic of China (PRC) are used to model the crime-income distribution relationship. Income polarization is found to be positively and significantly associated with crime. When both income polarization and inequality indicators are included in the models, the former remains a positive and significant determinant while the latter becomes insignificant.
Keywords: D31; K4; 330; Economics; Poverty; China; People's Republic of